Batik Banyuwangi: Aesthetic and Technical Comparison of Coastal Batik - Qiram, Ikhwanul; -, Buhani; Rubiono, Gatut (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2018)
Banyuwangi, a district located in eastern end of Java island has batik as cultural herritage. Batik Banyuwangi as well as other batik has own characteristic according to the origin of the region. In the other side, Banyuwangi has a ethnics origin which is Osing ethnic with own character and local wisdom. Batik Banyuwangi is a kind of batik Pesisiran as batik from coastal region. Batik Pesisiran has a specificity in terms of material and method. Batik Banyuwangi has an interesting spesificity and become distinguishing identity of batik from other area. This research is aimed to compare batik Banyuwangi characteristic with other batik Pesisiran by literature study method. The result shows that batik banyuwangi has own aesthetics (motive and meaning) comparing with other batik Pesisiran. From technical aspect (material and method), batik Banyuwangi have in common with other batik Pesisiran.